Multiphysics modeling and validation of a microwave applicator with a three-stub tuner for the continuous flow pasteurization of fruit juices with low reflection - Guilherme Russo; Jorge A. W. Gut; Jorge A. W. Gut; Dorin Boldor (Frontiers in Sustainable Food Systems)
Microwave heating technology offers several advantages for the continuous flow pasteurization of fluid foods compared to conventional heat exchangers. These advantages include rapid and volumetric heating, high energy efficiency allowing for using electricity from sustainable sources, and reduced sensory and quality loss. In fruit products, where the low pH inhibits the growth of harmful microorganisms, the primary thermal targets for pasteurization are heat-resistant enzymes such as peroxidase, polyphenol oxidase, and pectin methylesterase. The microwave applicator can quickly heat the product stream to the enzyme inactivation temperature, followed by a holding period to achieve the desired level of enzyme inactivation. The modeling and simulation of the microwave applicator is particularly challenging because it requires the coupling of three physical phenomena: propagation of electromagnetic radiation, fluid flow, and heat generation and heat transfer. Temperature-dependent changes in the product’s dielectric properties affect radiation penetration, thereby influencing heat generation. In this study, a multiphysics model was developed in COMSOL v.5.3 to numerically simulate the heating of orange juice (OJ), mango puree (MP), and mango juice (MJ; flow rate: 0.2–1.2 L/min; outlet temperature: 70–100°C) in the cavity of a pilot-scale microwave-assisted pasteurizer. The dielectric properties of the products were measured, and the model was validated against experimental results. The microwave cavity, an octagonal prism with a vertical applicator tube, is linked to a 6-kW microwave generator operating at 2.45 GHz. The model includes the waveguide and a three-stub tuner, an element seldom integrated into similar models. Simulation results provide insights into the distribution of the electric field in the domain, temperature profiles in the product, and losses of incident power due to reflection. Using the principles of electromagnetism and the Monte Carlo method, the stub heights in the tuner were optimized to minimize power reflection, quantified by the scattering parameter (S11). Seventeen processing conditions, varying in product types, temperatures, and flow rates, were simulated and compared with experimental data. The model demonstrated an overall prediction error of 1.6 ± 1.3°C for the outlet temperature of orange juice, while errors for mango purée and mango juice ranged between 1.8 and 5.5°C. The validated model serves as a valuable tool for the analyzing, designing and optimizing the microwave applicators. As an example, it was used to evaluate the influence of the cavity cross-section shape and tube positioning on power reflection and heating uniformity.